2005
DOI: 10.1590/s1516-35982005000500027
|View full text |Cite
|
Sign up to set email alerts
|

Desempenho e características de carcaça de novilhos alimentados com dietas contendo diferentes fontes de lipídios

Abstract: RESUMO -Este trabalho foi realizado para se avaliar o desempenho animal, as características da carcaça e a maciez da carne de 36 novilhos mestiços, apresentando, ao início do experimento, média de 14 meses de idade e aproximadamente 320 kg de peso vivo. Os animais foram confinados e receberam dietas com alto teor de concentrado: uma controle (CO), sem adição de lipídios; outra contendo 5% de sais de cálcio de ácidos graxos (AG); e outra com 21% de caroço de algodão (CA). A ingestão de matéria seca no tratament… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
17
2
24

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 15 publications
5
17
2
24
Order By: Relevance
“…Similarily, Aferri et al (2005) found average daily weight gain values of 1.17 kg/d and feed conversion values of 8.38 kg of DM/kg in diets with 5% calcium salts and the addition of fatty acids. They also reported average daily weight gain values of 1.20 kg/d and feed conversion values of 7.86 kg DM/kg gain in diets with 21 g/kg cottonseed.…”
Section: Resultssupporting
confidence: 70%
See 2 more Smart Citations
“…Similarily, Aferri et al (2005) found average daily weight gain values of 1.17 kg/d and feed conversion values of 8.38 kg of DM/kg in diets with 5% calcium salts and the addition of fatty acids. They also reported average daily weight gain values of 1.20 kg/d and feed conversion values of 7.86 kg DM/kg gain in diets with 21 g/kg cottonseed.…”
Section: Resultssupporting
confidence: 70%
“…This implicates that the mechanism of physiological regulation may justify the greater intake of the diet with protected fat when compared with the diet with other lipid supplements. Aferri et al (2005) found similar DM intake values calculated as percentage of body weight. They fed 14-monthold confined crossbreed steers with diets containing either 5 g/kg fatty acid calcium salts or 21 g/kg cottonseed, and the DM intake values were 2.45 g/kg and 2.29 g/kg, respectively.…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…Sabe-se que a deposição de gordura na garupa ocorre mais precocemente que nas costelas (Yokoo et al, 2008); por esse motivo, a área da garupa é local indicado para se verificar as reservas corporais prontamente disponíveis (Maciel, 2006). Aferri et al (2005) observaram que a inclusão de 21% de caroço de algodão na dieta não influenciou o peso e o rendimento de carcaça, a AOL e a EGC, obtidas por ultrassom. O mesmo fato foi observado por Pesce (2008) em relação a essas variáveis, como também em relação à P8.…”
Section: Resultsunclassified
“…Aferri et al ( 2005), com bovinos confinados, observaram que o caroço de algodão utilizado em até 21% nas rações não alterou o desempenho animal.…”
Section: Resultsunclassified